Shine on, Luz Véliz! - Balcárcel, Rebecca (Chronicle Books LLC, 2022)
Eleven-year-old injured soccer player Luz has a hard enough time reframing her identity as a computer programmer, but when her Guatemalan half-sister moves in, she learns what it truly means to start over. Includes author's note.